Generative Design of a Mechanical Pedal - Nisar, Mohammad Musa; Zia, Salman; Fenoon, Mahmoud; Alquabeh, Omar (International Journal of Engineering and Management Sciences, 2021)
Nowadays, there are various tools that support the initial stages of design available to use for engineers, the traditional Computer-Aided Design (CAD) has been implemented in the engineering components design and replaced manual drafting. However, with the advances and the rapid technology development, new trends emerged to cope with this evolution, namely, Generative Design, Topology Optimization, and Generative Engineering Design. The method is based on numerical algorithms that generate a variety of design and modelling options based on the criteria and constraints set by the designer to allow further design exploration. Proposed in this paper is an implementation of the generative design of a mechanical pedal with further finite element analysis.